Anti-Colitic Effects of Kanjangs (Fermented Soy Sauce and Sesame Sauce) in Dextran Sulfate Sodium-Induced Colitis in Mice - Song, Jia-Le (Mary Ann Liebert, Inc., 2014)
This study was conducted to investigate the preventive effects of different kanjangs (Korean soy sauces), including acid-hydrolyzed soy sauce (AHSS), fermented soy sauce (FSS), and fermented sesame sauce (FSeS), on 2% dextran sulfate sodium (DSS)-induced ulcerative colitis in C57BL/6J mice. The fermented sauces, particularly FSeS, significantly suppressed DSS-induced body weight loss, increased colon length, and decreased colon weight/length ratios. Histological observations suggested that the fermented sauces prevented edema, mucosal damage, and the loss of crypts induced by DSS compared to the control mice and animals fed AHSS. FSeS and FSS decreased the serum levels of tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), interleukin (IL)-6, and IL-17α. mRNA expression of these cytokines as well as that of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in colon mucosa was also inhibited by the two sauces. Our results suggest that fermented sauces, especially FSeS, exert an anticolitic effect partially by reducing the serum levels of proinflammatory cytokines and inhibiting the mRNA expression of these factors in the colon tissue of mice treated with DSS. However, AHSS did not protect against DSS-induced colitis. In addition, low-dose treatment (4 mL/kg) with the fermented sauces resulted in greater anticolitic effects than consumption of a high quantity (8 mL/kg) of the sauces.